The Impact of One Parent Family Payment Reforms on the Labour Market Outcomes of Lone Parents - Paul Redmond; Seamus McGuinness; Claire Keane (Institute of Labor Economics (IZA), 2020)
This paper evaluates the impact of a reduction in the child qualifying age criteria for the One Parent Family Payment (OFP) in Ireland. From 2012 to 2015, the child qualifying age for OFP was reduced from 18 years to 7 years. Lone parents who no longer qualified for the payment, based on the age of their child, could avail of Jobseekers Transitional Payment (JST), which involves a labour activation component. While OFP recipients are subject to a maximum weekly earnings limit, there is no such limit for JST recipients, meaning that lone parents on JST had some capacity to increase their hours worked and thereby increase their income from employment. We find that these reforms led to an average increase in the hours worked of lone parents of between two and five hours per week. Two and a half years following the reform, lone parents impacted by the policy were 12 percentage points more likely to be working. In addition, we find an increase in household income of between 8 and 12 percent, and an increase of between 20 and 29 percent in earnings from employment. Finally, the policy was associated with a 10 to 13 percentage point reduction in the poverty rate of lone parents.
Keywords: H20; H31; J01; J68; 330; lone parents; policy reform; employment